Development of massively parallel nanolithography - Lee, Sharon Mei Yi. (2013)
As technology is becoming more and more advanced every day, lithography techniques are also moving towards nanoscale production of components needed in integrated electronic circuits, micro electrochemical systems (MEMS) and in medical and biology field etc. An ideal lithography method is essential to obtain high resolution patterns over to meet the rising needs of technology.